Diketopyrrolopyrrole derivatives-based NIR-II fluorophores for theranostics. (September 2021) - Zhang, Qin; Wang, Qi; Xu, Xingpeng; Liu, Jiawei; Lu, Xiaomei; Huang, Wei; Fan, Quli
Abstract: Because of reduced absorption and scattering, as well as negligible auto-fluorescence, near-infrared II (NIR-II, 1000–1700 nm) fluorescence imaging has become a cutting-edge platform for in vivo bioimaging. Organic molecules possess many intrinsic properties, such as high biosafety, fast excretion, and low toxicity, making them suitable candidates for in vivo application. Diketopyrrolopyrrole (DPP) derivatives have attracted considerable attention as theranostic agents for near-infrared I (NIR-I; 700–900 nm) fluorescence imaging or photoacoustic imaging guided therapy. Nevertheless, the construction of DPP-based NIR-II fluorophores has been scant until now. In this review, we presented the progress of DPP derivatives-based NIR-II fluorophores that developed by our group and their applications in bioimaging and theranostics. Furthermore, the challenges of these NIR-II fluorophores are discussed. Graphical abstract: This review presents the recent progress of diketopyrrolopyrrole derivatives-based NIR-II fluorophores that developed by our group and their applications for theranostics. Image 1 Highlights: NIR-II FL imaging can provide better imaging qualities, deeper tissue penetration, and higher signal-to-noise ratio. The review highlights the progress of DPP derivatives-based NIR-II fluorophores for theranostics. Offer valuable insights to design high performance NIR-II fluorophores by molecular engineering approach.